KEHIDUPAN PRIVAT DAN KETERTIBAN UMUM DALAM PUSARAN HUKUM - Subkhan, Achmad (Balai Diklat Keagamaan Surabaya, 2018)
Law develops in line with the development of society. A rule of lawmay be established before an event occurs, or vice versa. In thecontext of social life -in a broader scope includes the life of thenation and the state- law and its changes are born from certainprocedures that are based on an event. The law binds each memberand becomes a common reference of building life. Initially the realmof private life almost covers all aspects and has a clear limit. Forexample is the pattern of life of the empire / kingdom that tends tobe very exclusive strongly supports the pattern of life that isindividualistic. This study aims to examine the pattern of changesin jurisdiction. In line with the purpose of research, research methodusing descriptive method with qualitative approach. The type ofresearch is the library research the source data is library materialsthat are analyzed by content analysis (content analysis). The resultsof this study indicate that in the development of the private lifedomain becomes increasingly narrow due to the increasinglycomplex social interaction. The area of private life becomesincreasingly narrow, while the public realm becomes wider.